Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s13293-022-00481-9
|View full text |Cite
|
Sign up to set email alerts
|

Plasma TIMP-1 as a sex-specific biomarker for acute lung injury

Abstract: Background Acute respiratory distress syndrome (ARDS) confers high morbidity and mortality, with a death rate reaching 40%. Pre-clinical and clinical studies have cited sex-specific sex hormones as a critical contributor to divergent immunologic responses. Therefore, exploration of sex and sex hormone roles following lung injury and ARDS development is needed. Tissue inhibitor of metalloproteinase-1 (TIMP-1) was the first-discovered natural collagenase inhibitor and is located exclusively on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…Tissue inhibitor of metalloproteinase-1 (TIMP-1) is a biomarker of relevance to extracellular matrix turnover, and plays a key role in the control of matrix metalloproteinases (MMPs), which are responsible for the breakdown of extracellular matrix components. Maintaining a proper equilibrium between MMPs and TIMPs is fundamental for tissue homeostasis, and the disruption of this balance has been associated with specific pathological processes, including ALI and ARDS [94].…”
Section: Tissue Inhibitor Of Metalloproteinase-1 (Timp-1)mentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue inhibitor of metalloproteinase-1 (TIMP-1) is a biomarker of relevance to extracellular matrix turnover, and plays a key role in the control of matrix metalloproteinases (MMPs), which are responsible for the breakdown of extracellular matrix components. Maintaining a proper equilibrium between MMPs and TIMPs is fundamental for tissue homeostasis, and the disruption of this balance has been associated with specific pathological processes, including ALI and ARDS [94].…”
Section: Tissue Inhibitor Of Metalloproteinase-1 (Timp-1)mentioning
confidence: 99%
“…Almuntashiri et al's study showed that high levels of plasma TIMP-1 are linked to ALI in female patients, whereas no such association was observed in male patients. This emphasizes the need to take gender differences into account when examining biomarkers for ARDS and other lung injuries [94].…”
Section: Tissue Inhibitor Of Metalloproteinase-1 (Timp-1)mentioning
confidence: 99%